Generating Fake News Detection Model Using a Two-Stage Evolutionary Approach - Cheni Sruneethi; Moduru Mounika (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
While fake news is morally reprehensible, irresponsible parties intentionally use it to achieve their goals by disseminating it to vulnerable and targeted groups. Machine learning techniques have been researched extensively to detect fake news. On the other hand, evolutionary-based algorithms are now gaining popularity in the research community. In this study, a two-stage evolutionary approach is proposed to generate and optimize a mathematical equation for fake news detection. In the first stage, tree-based Genetic Programming (GP) algorithm is used to generate mathematical expressions to detect correlations between the language-independent (Lang-IND) features, extracted from Fake.my-COVID19 dataset, the newly curated fake news dataset in a mixed Malay - English language. The uniqueness of the proposed approach is that the mathematical expressions are formed by basic arithmetic operators or to include complex arithmetic operators such as addition, multiplication, subtraction, division, square, abs, log1p, sign, square root, and exponential together with Lang-IND features as the variables. Prior to second stage of the evolutionary approach, a sensitivity analysis is applied to shorten the best equation while maintaining the F1-score performance. In the second stage, an Adaptive Differential Evolution (ADE), is used to fine-tune the mathematical model.